A polymorphism in PRF1 gene is associated with HIV-1 vertical transmission in Brazilian children. - Padovan, Lara; Segat, Ludovica; Crovella, Sergio (AIDS, 2011)
We investigated the possible association between PRF1 gene polymorphisms and HIV-1 vertical transmission in Brazilian children by analyzing PRF1 gene coding and untranslated regions in 173 perinatally infected children (HIV+), 51 exposed uninfected (HIV-), and 171 HIV-unexposed uninfected children. Seven single nucleotide polymorphisms were identified in our samples. The rs885822 C allele and CC genotype were significantly more frequent in HIV-negative than in HIV-positive patients and associated with a protective effect toward HIV vertical transmission.
Keywords: Brazil; Female; HIV Infections; HIV-1; Humans; Infant, Newborn; Infectious Disease Transmission, Vertical; Male; Polymorphism, Genetic; Pore Forming Cytotoxic Proteins; Pregnancy